2020
DOI: 10.1139/cjz-2019-0207
|View full text |Cite
|
Sign up to set email alerts
|

A review of Canadian Arctic killer whale (Orcinus orca) ecology

Abstract: The killer whale (Orcinus orca (Linnaeus, 1758)) is a widely distributed marine predator with a broad ecological niche at the species level with evidence of specialization and narrow ecological niches among populations. Their occurrence in Canadian Arctic waters is limited by sea ice and it has been suggested that climate warming, which has caused increases in the area of ice-free water and duration of the ice-free season, has led to an increased killer whale presence during the open-water period. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…In-depth study of biochemical pathways and gene expression are also likely to clarify the paths from genotype to phenotype for environmental adaptations (Cheviron & Brumfield, 2012). As an example of the pro- Although certain killer whale ecotypes are relatively well known, additional information is needed for conservation management, especially for populations that are logistically more difficult to study (de Bruyn et al, 2013;COSEWIC, 2008;Lefort et al, 2020;Riesch et al, 2012). To date, extensive research has nonetheless demonstrated the existence of genetically divergent units that differ in behaviour, diet, phenotype, group size and vocalization patterns (e.g.…”
Section: Application Of the Ecotype Concept To Conserve Locally Adapt...mentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth study of biochemical pathways and gene expression are also likely to clarify the paths from genotype to phenotype for environmental adaptations (Cheviron & Brumfield, 2012). As an example of the pro- Although certain killer whale ecotypes are relatively well known, additional information is needed for conservation management, especially for populations that are logistically more difficult to study (de Bruyn et al, 2013;COSEWIC, 2008;Lefort et al, 2020;Riesch et al, 2012). To date, extensive research has nonetheless demonstrated the existence of genetically divergent units that differ in behaviour, diet, phenotype, group size and vocalization patterns (e.g.…”
Section: Application Of the Ecotype Concept To Conserve Locally Adapt...mentioning
confidence: 99%
“…Genomic analyses of killer whale ecotypes have reported adaptive variation associated with several traits linked to environmental variation, including cold adaptation, dietary variation and reproductive function (Foote et al, 2016 ). Forthcoming research combining genomics, satellite tracking, dietary analyses and other data can offer further resolution on killer whale evolutionary history (Whitehead, 2017 ), including ecotypes that have so far proved more difficult to study (COSEWIC, 2008 ; Lefort et al, 2020 ) and populations where patterns of possible ecological divergence are currently less clear (de Bruyn et al, 2013 ; Tavares et al, 2018 ). Killer whale ecotypes may now represent incipient (sub)species (Morin et al, 2010 ; Moura et al, 2015 ; Whitehead, 2017 ).…”
Section: A Framework and Recommendations For Incorporating Genetic St...mentioning
confidence: 99%
“…Killer whales, Orcinus orca, are apex marine predators that occupy every ocean (Heyning and Dahlheim 1988). All killer whales currently belong to the same taxonomic group, but sympatric and geographically separated populations of killer whales vary in their genetic make-up (see Morin et al 2010 for proposed taxonomic differentiation based on phylogenetic analysis), behavioural ecology (diet, social structure, movement patterns and dialects) and morphology (Hoelzel and Dover 1991, Ford et al 1998, Pitman and Ensor 2003, Pitman et al 2010, de Bruyn et al 2013, Durban et al 2016, Lefort et al 2020. Populations of killer whales with different ecological adaptations can be differentiated into ecotypes.…”
mentioning
confidence: 99%
“…Regardless, allopatric populations of killer whales often occur in oceans with markedly different environmental conditions and prey species availability. This variability has resulted in substantial ecological variation in this species reflected in the dietary specialisation of many killer whale populations with some being highly specialised fish or mammal predators while others are more generalist predators (Ford et al 1998, Pitman and Ensor 2003, Pitman et al 2010, de Bruyn et al 2013, Durban et al 2016, Lefort et al 2020. Local prey availability and dietary specialisation may lead to variation in social and demographic patterns across populations and impact the viability or persistence of (sub)populations.…”
mentioning
confidence: 99%
“…There is well‐developed literature on polar bears and climate change, with concerns that current and projected loss of habitat could have demographic and physiological consequences for polar bears, such as reduced survival, abundance, and reproductive survival (Laidre et al, 2020; Pagano et al, 2018), although not all regions are equally at risk (Krupnik, 2018; Regehr et al, 2018). Other ice‐dependent species identified to be at risk include walrus, sea birds, and different seal species (Huntington et al, 2020; Krupnik, 2018), while ice retreat has opened new habitat for cetaceans with increased sightings of killer whales noted in a number of regions (Lefort et al, 2020; Stafford, 2019) along with earlier seasonal migration of some species (Huntington et al, 2020). Many of these species have significant cultural value and are important in Indigenous food systems.…”
Section: Marine and Terrestrial Environments Are Experiencing Unprecedented Climate Impactsmentioning
confidence: 99%